Perawatan Kerusakan Impeller Pompa Air Laut Pada Sistem Pendingin Kapal Km. Sabuk Nusantara 101: Perawatan Kerusakan Impeller Pompa Air Laut Pada Sistem Pendingin Kapal Km. Sabuk Nusantara 101 - Pereira Maia Pinto, Gaspar; Bilak Lopo, Elkana; Adam Tnunay, Imanuel; Nisen Laosana, Okto Rosario; Hakim, Moh. Lukman; Bayu Bou, William Mathew (Blueprint Journal, 2025)
The seawater pump is a vital component of a ship’s cooling system, functioning to circulate seawater as the primary cooling medium for the main engine and generators. One of its main parts, the impeller, operates continuously in direct contact with seawater and is therefore highly susceptible to damage caused by corrosion, cavitation, and material wear. This study aims to analyze the causes of pressure reduction in seawater pumps, identify damages to centrifugal pump impellers, and determine the factors contributing to the reduced suction capacity of seawater pumps on board KM. Sabuk Nusantara 101. The research applied a qualitative descriptive-analytical method, combining direct observation, interviews with engine crew, documentation, and literature review. The study was conducted during the voyage of KM. Sabuk Nusantara 101 from April 28 to May 10, 2025, covering the route from Kupang through Atapupu, Maritaeng, Kalabahi, Baranusa, Balauring, Lewoleba, Waiwerang, Larantuka, to Maumere. Data were analyzed by comparing the actual pump condition with the standard operating parameters of the ship’s cooling system. The results revealed that the reduction in pump pressure (0.14 MPa compared to the standard 0.2–0.4 MPa) was caused by impeller damage, blockage in the suction line, and pipe leakage. The examined impeller showed severe damage, including corrosion, broken vanes, and increased clearance between the impeller and casing. These conditions led to a significant decrease in pump efficiency and suction performance. Other contributing factors were air leakage in the suction line, biofouling at the seawater intake, and insufficient routine maintenance. In conclusion, impeller failure and system leakage are the primary factors reducing the performance of seawater pumps in the ship’s cooling system. Preventive maintenance such as regular sea chest cleaning, impeller inspection, replacement of worn components, and ensuring airtight suction lines is essential. These efforts are crucial to maintaining the reliability of the cooling system, preventing engine overheating, and ensuring the safety of ship operations.